Historical Exploration: Soerakarta Walking Tour as a Platform to Foster Historical Awareness of BSLady Solo - Nurpratiwi, Hany; Amir, Nor Zana Binti Mohd; Mumpuni, Restu Ayu; Rusdini, Siti Ekowati (Universitas Negeri Semarang, 2025)
The historical exploration program, initiated through a collaboration between BSLady Solo and Soerakarta Walking Tour, serve as a transformative model for integrating cultural heritage education with community engagement. Aimed at exchanging historical awareness among urban women's fashion communities, the program immerses participants in Solo's historical landscape while deepening their understanding of batik as cultural and philosophical artifact. Through guided exploration and narrative based learning, participants not only discover the craftsmanship that shapes Solo's identity. This initiative demonstrates how culturally immersive and participatory methods can bridge generational gaps, promote local wisdom and stimulate cultural continuity in rapidly modernizing society. The program underscores the potential of creative heritage collaborations in fostering a sustainable appreciation of local identity and in cultivating a sense of collective pride in cultural traditions.